2008
DOI: 10.1080/09593330801987111
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Analysis of Dispersed Oil and Oil‐mineral Aggregates With an Automated Ultraviolet Epi‐fluorescence Microscopy System

Abstract: This paper describes recent advances in microscopic analysis for quantitative measurement of oil droplets. Integration of a microscope with bright-field and ultraviolet epi-fluorescence illumination (excitation wavelengths 340-380 nm; emission wavelengths 400-430 nm) fitted with a computer-controlled motorized stage, a high resolution digital camera, and new image-analysis software, enables automatic acquisition of multiple images and facilitates efficient counting and sizing of oil droplets. Laboratory experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…1998;Tkalich and Chan, 2002;Shaw, 2003). The effects of mixing energy on dispersed oil droplet size distributions, and consequently dispersant effectiveness, have been reported in laboratory tests (Byford et al, 1984;Lewis et al, 1985;Sorial et al, 2004;Chandrasekar et al, 2005;Ma et al, 2008) and in field trials under low-and high-energy regimes caused by various wind effects (Lunel, 1993(Lunel, , 1995. The droplet size distributions are also affected by the collision frequency, which has been considered a function of system hydrodynamics, and collision efficiency, which is generally believed to represent the chemistry involved in the coalescence reactions.…”
Section: Introductionmentioning
confidence: 91%
“…1998;Tkalich and Chan, 2002;Shaw, 2003). The effects of mixing energy on dispersed oil droplet size distributions, and consequently dispersant effectiveness, have been reported in laboratory tests (Byford et al, 1984;Lewis et al, 1985;Sorial et al, 2004;Chandrasekar et al, 2005;Ma et al, 2008) and in field trials under low-and high-energy regimes caused by various wind effects (Lunel, 1993(Lunel, , 1995. The droplet size distributions are also affected by the collision frequency, which has been considered a function of system hydrodynamics, and collision efficiency, which is generally believed to represent the chemistry involved in the coalescence reactions.…”
Section: Introductionmentioning
confidence: 91%
“…The mixing time, or the amount of time that the oil and sediment is subjected to turbulent conditions, also has an effect on OPA formation. Droplet stabilization in OPAs occurs relatively fast, typically taking less than 24 h, and often occurring within 1–3 h under laboratory conditions (Hill et al, ; Ma et al, ; Sun et al, ). Several studies have shown that the amount of oil dispersed as OPAs rapidly increases initially, but levels out over time (Payne et al, ; Sun et al, , ).…”
Section: Formationmentioning
confidence: 99%
“…Since the basic components of microscopic and macroscopic oil‐sediment residues are the same (oil and sediment), it is reasonable to expect that the variables that affect the formation of microscopic aggregates would also affect macroscopic agglomerate formation, albeit not necessarily to the same extent. For example, there have been several studies on how mixing energy affects the rate and degree of OPA formation (Ma et al, ; Payne et al, ; Sun et al, , ); however, beyond the conceptual idea that breaking waves facilitate SOA and SOM formation, there is no consensus in the macroscopic community about how more turbulent nearshore environments might affect macroscopic agglomerate formation. Similarly, several studies have been carried out to understand how the likelihood of OPA formation differs for different types of oils (Gustitus et al, ; Guyomarch et al, ; Kepkay et al, ; Khelifa et al, ; Omotoso et al, ; Sørensen et al, ; Stoffyn‐Egli & Lee, ); however, the macroscopic community has not carried out any such controlled studies, although it could be assumed that oil qualities such as density, polarity, and viscosity would have a significant impact on macroscopic agglomerate formation.…”
Section: Formationmentioning
confidence: 99%
“…McDonough and coworkers [173] developed HCA techniques to analyze LDs in 96well dishes ± rosiglitazone, a PPAR agonist that promotes adipogenesis. Comparable approaches were described by others [175][176][177]. Similarly, Whittaker and his colleagues [174] imaged LD size and number with an automated digital microscopy workstation to screen the potential of miRNAs to reduce TG accumulation in human Huh7 hepatocytes.…”
Section: High Resolution Confocal Microscopymentioning
confidence: 99%